2023
DOI: 10.4239/wjd.v14.i4.364
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic role of growth factors in treating diabetic wound

Abstract: Wounds in diabetic patients, especially diabetic foot ulcers, are more difficult to heal compared with normal wounds and can easily deteriorate, leading to amputation. Common treatments cannot heal diabetic wounds or control their many complications. Growth factors are found to play important roles in regulating complex diabetic wound healing. Different growth factors such as transforming growth factor beta 1, insulin-like growth factor, and vascular endothelial growth factor play different roles in diabetic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 390 publications
0
9
0
1
Order By: Relevance
“…For example, TGF-β acts as a chemotactic protein of broblasts [13]. The expression of TGF-β receptors by broblasts involved in the wound healing has been examined in normal and healed skin, particularly in healing scars [10,57]. In this study, TGF-β was innovatively loaded into GDY/G NPs to be delivered in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, TGF-β acts as a chemotactic protein of broblasts [13]. The expression of TGF-β receptors by broblasts involved in the wound healing has been examined in normal and healed skin, particularly in healing scars [10,57]. In this study, TGF-β was innovatively loaded into GDY/G NPs to be delivered in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor β (TGF-β) is a cell factor that potentially helps wound healing [10]. It promotes the growth and migration of epidermal and vascular endothelial cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Standard wound care is not always effective to treat diabetic wounds because of all the cellular abnormalities caused by diabetes 29 . Nonhealing wounds lead to loss of function, anxiety, frustration, isolation and poor quality of life for those affected, and is associated with more frequent and prolonged hospitalization, which represent an economic burden to healthcare systems 1 .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon could be attribute to more than one mechanism. First, endothelial cells initiate angiogenesis in response to multiple pro-angiogenic signals such as VEGF, FGF-2, PDGF-B and TGF-b 3 , which are all downregulated in diabetic wounds 29,33 . It has been suggested that alterations in macrophage phenotype may be, in part, responsible for impaired neovascularization in diabetic wounds 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Процесс эффективного заживления ран требует активного участия нейтрофилов, экспрессирующих паттерн-распознающие рецепторы для микробных и патоген-ассоциированных молекул (MAMP/PAMP microbe-/ pathogen-associated molecular pattern), а также паттерны повреждённых клеток (DAMP, damage-associated molecular pattern) [2,6]. Такие клетки фагоцитируются макрофагами посредством интегринов β2, что индуцирует в них высвобождение TGF-β 1 , который стимулирует дифференцировку миофибробластов, способствуя синтезу коллагена и уменьшению площади повреждения [9]. Присутствие нейтрофилов в месте повреждения, как правило, ограничивается фазой активного воспаления; их более длительное присутствие при физической травме и/или продолжающемся заражении оказывает вредное воздействие и препятствует эффективному заживлению ран [2, 10].…”
Section: нейтрофилыunclassified